2008
DOI: 10.1111/j.1365-3148.2007.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, single‐blind, increasing dose safety trial of an oxygen‐carrying plasma expander (Hemospan®) administered to orthopaedic surgery patients with spinal anaesthesia

Abstract: The objective of this study was to further explore the safety of Hemospan (Sangart Inc., San Diego, CA, USA), an oxygen-carrying plasma expander. The aim of this study was to determine if Hemospan is well tolerated in orthopaedic surgery patients with spinal anaesthesia in doses up to 1 L. Hemospan was previously found to be well tolerated in normal volunteers and orthopaedic surgery patients with spinal anaesthesia in doses up to 500 mL. Five cohorts of six orthopaedic surgery patients, American Society of An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…Interestingly, serum Hp completely disappeared immediately after MP4 administration, suggesting that MP4 was captured by Hp and eliminated via CD163, similar to endogenous Hb [8], albeit PEG would be expected to prevent the interactions between Hp and Hb. Olofsson et al reported two randomized Phase II studies that were carried out to evaluate the safety and efficacy of MP4 at a dose of 100–500 mg/kg during spinal anesthesia in patients who were undergoing orthopedic surgery [57,58]. The half-life of MP4 in these patients ranged from 14 to 23 h, which was prolonged with increasing dose.…”
Section: Acellular Type Hbocsmentioning
confidence: 99%
“…Interestingly, serum Hp completely disappeared immediately after MP4 administration, suggesting that MP4 was captured by Hp and eliminated via CD163, similar to endogenous Hb [8], albeit PEG would be expected to prevent the interactions between Hp and Hb. Olofsson et al reported two randomized Phase II studies that were carried out to evaluate the safety and efficacy of MP4 at a dose of 100–500 mg/kg during spinal anesthesia in patients who were undergoing orthopedic surgery [57,58]. The half-life of MP4 in these patients ranged from 14 to 23 h, which was prolonged with increasing dose.…”
Section: Acellular Type Hbocsmentioning
confidence: 99%
“…In a phase II study of 90 patients undergoing orthopedic surgery under spinal anesthesia, the infusion of up to 500 mL Hemospan reduced the frequency of hypotensive episodes to 45-48% (vs. 87% in the control-group). Three serious adverse events, including two deaths were reported, but none was considered related to study treatment [67,68]. The effect of Hemospan™ on hypotension after induction of spinal anesthesia was also studied in a recently completed phase-III trial, which compared the volume expansion effect of Hemospan™ with a hydroxyethyl starch preparation (6% HES 130/0.4).…”
Section: Hbocmentioning
confidence: 98%
“…However, nonclinical and clinical studies of HBOCs have raised questions about their safety, presenting an obstacle to their development [17,18,19]. Thus, in addition to improving the quality of HBOCs themselves, we have started to explore their alternative clinical uses [12,13,20].…”
Section: Discussionmentioning
confidence: 99%